Deriving strategic information for software development processes using provenance data and ontology techniques - Costa, G.C.B.; Werner, C.; Dalpra, H.L.O.; Braga, R.; Araújo, M.A.P.; Ströele, V. (International Journal of Business Process Integration and Management, 2019)
Processes improvement is a key feature to achieve quality in products. The investments in defining and refining organisations’ processes are always a concern. This fact also occurs in the software development processes domain. A practice considered to support the continuous improvement of software processes is the reuse of knowledge acquired in previous executions. A way to capture this knowledge is by using provenance models. The main goal of this work is to define, implement and evaluate the iSPuP approach to support the phases of execution, monitoring, analysis, and feedback of processes, using provenance data and ontology techniques, to derive strategic information that can be used to improve software process in future executions. An evaluation was carried out with two software development companies and the results have shown initial evidences that iSPuP can derive strategic information and the project manager will be able to use them for improving process performance runtime.